Linked color imaging improves the endoscopic visibility of gastric mucosal cancers - Kitagawa, Yoshiyasu; Suzuki, Takuto; Hara, Taro; Nankinzan, Rino; Takashiro, Hideyuki; Sugita, Osamu; Imazeki, Hiroshi; Yamaguchi, Taketo (Endoscopy International Open, 2019)
Background and study aims As a newly developed endoscopy technique, linked color imaging (LCI) provides very bright images with enhanced color tones. With the objective of improving the detection rate of gastric mucosal cancers, which are often difficult to detect, we examined the utility of LCI from the viewpoint of visibility.Patients and methods The current study used 100 consecutive gastric mucosal cancers ≤ 20 mm in diameter. For each lesion, we selected one endoscopic image acquired by white-light imaging (WLI), blue-laser imaging (BLI) -bright, and LCI modes. Four endoscopists interpreted the images; using a previously reported scale, we scored the visibility level on a scale of 1 – 4.Results The mean (± SD) visibility scores were 2.54 ± 1.10 for WLI, 3.02 ± 1.07 for BLI-bright, and 3.28 ± 0.97 for LCI. The score was significantly higher for BLI-bright compared with WLI (P < .001) and again higher for LCI compared with BLI-bright (P < .001). For the experts, the scores for BLI-bright and LCI were similar, but both were significantly higher than the score for WLI. For the trainees, there was no significant difference between the WLI and BLI-bright scores, but LCI score was significantly higher than those for WLI and BLI-bright scores. With regard to clinical characteristics, LCI particularly enhanced visibility of normochromic, flat and depressed lesions, which had the lowest visibility scores of all three modalities compared with those of the other lesions.Conclusion LCI increased visibility and may contribute to early detection of gastric mucosal cancers.